YKL-40 levels increase with declining ankle-brachial index and are associated with long-term cardiovascular mortality in peripheral arterial disease patients. (July 2018) - Höbaus, Clemens; Tscharre, Maximilian; Herz, Carsten Thilo; Pesau, Gerfried; Wrba, Thomas; Koppensteiner, Renate; Schernthaner, Gerit-Holger
Abstract: Background and aims: YKL-40 is an inflammatory marker secreted by macrophages and is expressed in atherosclerotic plaques. YKL-40 increases in coronary artery disease (CAD) with poor coronary collateral vessel development. Higher levels are linked to reduced survival in CAD patients. Studies evaluating YKL-40 in patients with peripheral arterial disease (PAD) are scarce. This study aims to elucidate a possible link between YKL-40 and PAD severity as well as cardiovascular long-term mortality. Methods: YKL-40 was measured at baseline in 365 elderly PAD patients (age 69 ± 10.4, 33.7% women, Fontaine stage I-II) by bead-based multiplex assay. Patients were followed for seven years to assess long-term cardiovascular and all-cause survival by Kaplan-Meier and Cox regression. Results: YKL-40 levels were associated with declining ankle-brachial index (ABI) in PAD patients without Moenckeberg's mediasclerosis (R = −0.189, p =0.002). PAD patients with mediasclerosis exhibited higher YKL-40 levels ( p =0.002). Baseline YKL-40 levels were significantly associated with cardiovascular mortality (HR 1.52 (1.21–1.91), p < 0.001) and all-cause mortality (HR 1.45 (1.20–1.75), p < 0.001) over a seven-year observation period. After multivariable adjustment for gender, patient age, known carotid artery disease, known coronary artery disease, smoking status, systolic blood pressure, HbA1c, low density lipoprotein cholesterol, estimated glomerular filtration rate, aspartate aminotransferase, and C-reactive protein, YKL-40 remained significantly associated with cardiovascular (HR 1.34 (1.02–1.75), p =0.033) and all-cause mortality (HR 1.25 (1.01–1.55), p =0.039). Conclusions: Increased YKL-40 levels are independently associated with poor long-term cardiovascular survival in peripheral arterial disease patients. Furthermore, YKL-40 correlates with patients' ABI in PAD in the absence of mediasclerosis. Highlights: YKL-40 levels increase with peripheral arterial disease (PAD) severity. Elevated YKL-40 is linked to reduced all-cause survival over 7 years in PAD. The association of YKL-40 on mortality was more pronounced in cardiovascular mortality in comparison to all-cause mortality.